Corporate Social Responsibility and Employee Engagement: Enabling Employees to Employ More of Their Whole Selves at Work - Glavas, Ante (Frontiers in Psychology, 2016)
Research at the individual level of corporate social responsibility (CSR) has been growing rapidly. Yet we still lack a more complete understanding of why and how individuals (i.e., employees) are affected by CSR. This study contributes to that gap by exploring the relationship between CSR and employee engagement. Moreover, in order to address the problem of low levels of employee engagement in the workplace, CSR is proposed and tested as a pathway for engaging a significant part of the workforce. Building on engagement theory, a model is tested in which CSR enables employees to bring more of their whole selves to work, which results in employees being more engaged. Data from 15,184 employees in a large professional service firm in the U.S. was analyzed using structural equation modeling. Results show that authenticity (i.e., being able to show one’s whole self at work) positively and significantly mediates the relationship between CSR and employee engagement. However, the other mediator tested in this study, perceived organizational support (POS; i.e., direct benefits to the employee), did not significantly mediate the relationship. In addition, results of moderated mediation suggest that when CSR is extra-role (i.e., not embedded in one’s job design such as volunteering), it weakens the relationship between CSR and employee engagement. Moreover, post hoc analyses show that even when POS is controlled for, authenticity has an impact above and beyond POS on employee engagement. These results extend prior CSR literature which has often been top-down and has focused on how employees will be positively affected by what the organization can give them (e.g., POS). Rather, a bottom-up approach might reveal that the more that employees can give of their whole selves, the more engaged they might be at work.